aadA Confers Streptomycin Resistance in Borrelia burgdorferi - Frank, Kristi L. (American Society for Microbiology, 2003)
To enhance genetic manipulation of the Lyme disease spirochete Borrelia burgdorferi, we assayed the aadA gene for the ability to confer resistance to the antibiotics spectinomycin and streptomycin. Using the previously described pBSV2 as a backbone, a shuttle vector, termed pKFSS1, which carries the aadA open reading frame fused to the B. burgdorferi flgB promoter was constructed. The hybrid flgB promoter-aadA cassette confers resistance to spectinomycin and streptomycin in both B. burgdorferi and Escherichia coli. pKFSS1 has a replication origin derived from the 9-kb circular plasmid and can be comaintained in B. burgdorferi with extant shuttle vector pCE320, which has a replication origin derived from a 32-kb circular plasmid, or pBSV2, despite the fact that pKFSS1 and pBSV2 have the same replication origin. Our results demonstrate the availability of a new selectable marker and shuttle vector for genetically dissecting B. burgdorferi at the molecular level.